Peran E-Government dalam Membangun Society 5.0: Tinjauan Konseptual terhadap Aspek Keberlanjutan Ekonomi, Sosial, dan Lingkungan - Shiddiq Sugiono (Research and Development Agency Ministry of Home Affairs, 2021)
Government agencies need to adapt to various technologies that developed in the Industrial Revolution 4.0. Not only in the technical aspect, but also in the social aspect of the use of technology, it must be brought up so that it can improve the quality of human life in a sustainable manner. Society 5.0 is present as a concept that is considered capable of bringing out the human side of the use of technology in the Industrial Revolution 4.0. E-government is considered to have relevance to society 5.0 where the use of technology is intended for the benefit of citizens. This conceptual research aims to provide an overview of the role of e-government in supporting the creation of society 5.0 through aspects of economic, social, and environmental sustainability. The method used to collect research data is a literature review and data analysis techniques through a qualitative approach. The results show that e-government is able to support sustainability in terms of economic, social and environmental aspects. From the economic aspect, e-government raises the effectiveness and efficiency of organizational performance so that a large volume of work can be done quickly using minimal resources. As for the social aspect, all people have equal access to quality public services. From the environmental aspect, e-government is considered capable of supporting various programs related to environmental conservation. A conceptual framework was also developed to provide an abstraction of the role of e-government in supporting society 5.0.